2015
DOI: 10.1002/acr.22513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Interleukin‐6 Level as a Surrogate Marker of Synovial Inflammation and as a Factor of Structural Progression in Early Rheumatoid Arthritis: Results From a French National Multicenter Cohort

Abstract: Objective. Interleukin-6 (IL-6) is a key cytokine in rheumatoid arthritis pathogenesis. We aimed to analyze the association between IL-6 serum levels and joint inflammation at baseline and the correlation of time-integrated IL-6 values with structural damage during the first 36 months of early arthritis. Methods. IL-6 was assessed by 2 different methods in 813 patients of the French early arthritis cohort ESPOIR (Etude et Suivi des Polyarthrites Indiff erenci ees R ecentes) over 36 months. IL-6 and C-reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
2
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 45 publications
4
41
2
6
Order By: Relevance
“…A meta-analysis demonstrated that only SJC and ESR were associated with radiographic progression [16]. Moreover, IL-6 levels, which are associated with structural damage, are strongly correlated with the SJC [17]. We found that the p value for SJC 1 decreased over time, suggesting that assessment of joint swelling by rheumatologists is generally reliable.…”
Section: Discussionmentioning
confidence: 65%
“…A meta-analysis demonstrated that only SJC and ESR were associated with radiographic progression [16]. Moreover, IL-6 levels, which are associated with structural damage, are strongly correlated with the SJC [17]. We found that the p value for SJC 1 decreased over time, suggesting that assessment of joint swelling by rheumatologists is generally reliable.…”
Section: Discussionmentioning
confidence: 65%
“…For example, high levels of IL-6 are associated with inflammation and joint damage in RA patients (35). Thus, the two pathologies share a clinical profile and high levels of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Как уже упоминалось выше, сохранение УЗ-призна-ков активного синовита, ведущего к прогрессированию рентгенологических изменений суставов, может ассоции-роваться с повышением исходного уровня ИЛ6 и СРБ, на-блюдавшимся в работе A. Baillet [16].…”
Section: таблицаunclassified
“…Учитывая ведущую роль этих патогенетических механизмов, проводились работы, по-священные изучению связи провоспалительных цитоки-нов и маркеров ангиогенеза [16], с УЗ-признаками, харак-теризующими состояние синовиальной оболочки при РА (табл. 2).…”
unclassified
See 1 more Smart Citation